2001
DOI: 10.1002/joc.627
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation trends over the Russian permafrost‐free zone: removing the artifacts of pre‐processing

Abstract: Rain gauge changes, changes in the number of observations per day, and inconsistent corrections to observed precipitation data during the 20th century of the meteorological network of the former Soviet Union make it difficult to address the issue of century time-scale precipitation changes. In this paper, we use daily and sub-daily synoptic data to account for the effects of these changes on the instrumental homogeneity of precipitation measurements over the Russian permafrost-free zone (RPF, most populous wes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 13 publications
0
42
0
1
Order By: Relevance
“…The current GPCC collection encompasses regional data sets for the former Soviet Union (Groisman et al, 1991;Groisman and Rankova, 2001) with data from 2186 stations for the period 1891-2001, updated to 2009 by a data set comprising 518 Russian stations (available from http://meteo.ru/english/climate/precip. php) described by Bulygina et al (2010).…”
Section: Appendix B List Of Contributions To Gpcc From National and Rmentioning
confidence: 99%
“…The current GPCC collection encompasses regional data sets for the former Soviet Union (Groisman et al, 1991;Groisman and Rankova, 2001) with data from 2186 stations for the period 1891-2001, updated to 2009 by a data set comprising 518 Russian stations (available from http://meteo.ru/english/climate/precip. php) described by Bulygina et al (2010).…”
Section: Appendix B List Of Contributions To Gpcc From National and Rmentioning
confidence: 99%
“…Analysis of daily precipitation makes use of archived station time series for the FSU assembled by Groisman and Rankova (2001). The complete archive contains 2187 stations, with records for some available as far back as 1891.…”
Section: Precipitationmentioning
confidence: 99%
“…From west to east, the watersheds are the Ob, Yenisey, Lena and Kolyma-Indigirka use records for the years 1960-92, which provides for a long period of overlap with reanalysis fields (see Section 2.2). The daily data are instrumentally homogeneous, but not bias adjusted (Groisman and Rankova, 2001). Bias adjustments relate primarily to gauge undercatch of blowing snow.…”
Section: Precipitationmentioning
confidence: 99%
See 1 more Smart Citation
“…Wetting losses can be significant depending on the gauge type and the number of observations per day and are commonly on the order of 2 -10% [Sevruk, 1982]. However, as will be seen in section 4.3, recent studies have shown that average wetting losses are not as high as previously thought and that incorrect assumptions have been applied for some bias adjustment efforts [Bogdanova and Mestcherskaya, 1998;Groisman and Rankova, 2001]. Evaporation losses vary by gauge type and the time of year (i.e., winter losses are less than summer losses), and usually range from 0.1 to 0.8 mm/d [Goodison et al, 1998] or between 0 and 4% of the measured precipitation [Sevruk, 1982].…”
Section: Introductionmentioning
confidence: 99%